THE EFFECT OF AEROBIC TRAINING IN RHEUMATOID ARTHRITIS PATIENTS: A LITERATURE STUDY - Hakim, Amelia Nurul; Widiyanto, Budi (Journal of Applied Health Management and Technology, 2021)
To evaluate the effectiveness of aerobic training on pain in Rheumatoid arthritis. Methods Asystematic literature search was carried out using the Pubmed, Embase, and Cochrane databases untilNovember 2016 and abstractly presented at a scientific meeting of rheumatology for 3 years. Randomizedcontrolled trials (RCTs) comparing resistance exercise-based therapy with interventions withoutresistance exercise for RA patients' treatment were included. Six literature studies, including 547 patients,met the study inclusion criteria. Patient characteristics and exercise did not affect the outcome. Subgroupanalysis revealed a trend toward higher effectiveness associated with high-intensity programs. There isevidence with a low risk of bias that an aerobic exercise program effectively reduces fatigue amongpatients with RA, especially in the short term. An RCT should be performed in patients with RA who areselected for fatigue to strengthen the evidence.